Elemental leaching from Quercus ilex L. in response to simulated acidic fog - Paoletti, E; Udisti, R; Pantani, F; Barbolani, E (Water, Air, & Soil Pollution, 1989)
Quercus ilex L. seedlings were intermittently exposed to simulated acidic and non-acidic fogs in 6-hr events for 16 times. After a 1-mo break, treatments were carried out again for a 5 day period. Strong acidity neutralization, weak acidity release and cation leaching from foliage and stem were determined. Leaching of AI, Cu, Mn, Fe, Cd, Pb, Ca, Mg, and K increased in response to acid treatment. This effect was less marked for Na. A positive correlation between H ÷ uptake and cation leaching was found. Cationic release and neutralization of strong acidity increased after breaks in acid treatment, but this faculty and the a m o u n t of leached cations and neutralized acidity decreased with time. The stem showed a higher cation loss and higher buffer capacity than the leaves.
Keywords: acidity; Cations (voyant); foliar leaching